2016
DOI: 10.5005/ijccm-20-9-530
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the role of single and multiple blood specimens in the outcome of blood cultures using BacT/ALERT 3D (automated) blood culture system in a tertiary care hospital

Abstract: Introduction: Bloodstream infection (BSI) is a leading cause of mortality in critically ill patients. The mortality directly attributable to BSI has been estimated to be around 16% and 40% in general hospital population and Intensive Care Unit (ICU) population, respectively. The detection rate of these infections increases with the number of blood samples obtained for culture. The newer continuous monitoring automated blood culture systems with enhanced culture media show increased yield and sensitivity. Hence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…About 2489 isolates were identi ed. The reason why the isolates exceeded the number of patients is that repeated blood specimen collection from a single patient is mandatory to increase the probability of isolate detection and to ensure that the isolate is not contaminant (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…About 2489 isolates were identi ed. The reason why the isolates exceeded the number of patients is that repeated blood specimen collection from a single patient is mandatory to increase the probability of isolate detection and to ensure that the isolate is not contaminant (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…This observation was seconded by several other studies in the literature. 6,7,12,21 The frequency distribution of pathogens (detection rate) isolated when collected in multiple sets was evaluated (Table 4). Out of all organisms isolated during the study period, only minor proportion (42-45%) were isolated from the BC episodes received with one BC bottle, as compared to the BC episodes received with ≤1 set (83-85%) and ≤2 sets (~98%) with a net gain of pathogen detection of about ~40% and ~13% when one set is collected compared to single bottle and 2 nd set is added to 1 st set BC respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant data collected were entered in Microsoft Excel and statistical analyses were performed with IBM SPSS Statistics V22.0 software. 12 The parameters used for the comparison of BC performance when collected in single bottle and multiple samples (1, 2 and 3 sets) have been defined in Table 1. The comparison of cumulative positivity rate, pathogen isolation rate, and pathogen detection rate between the episodes collected in single and multiple sets was carried out by using Kruskal-Wallis test (nonparametric).…”
Section: Data Collection and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In these settings, the conventional/ manual culture methods remain the dominant systems while the automated blood culture systems have become the standard in high-income countries (HICs), and are relatively expensive and not universally available for implementation in most LMICs where [7] [8] [9] implementing automated microbiologic systems is feasible [7] [10]. Several reports [11] [12] [13] in LMIC showed that these systems show better performance than manual systems in terms of yield, sensitivity and especially speed of growth and overall turnaround time. Blood cultures are still indispensable for the diagnosis of BSIs however currently available molecular methods based on in situ hybridization-based methods, DNA microarray-based hybridization technology; nucleic acid amplification-based methods and combined methods [14] are a distant prospect for LMICs.…”
Section: Introductionmentioning
confidence: 99%